Ecosystem Services and Cost-Benefit Analysis of Natural Forests and Mixed Bamboo Systems in Peru - Catpo Chuchón, J.E.; Cárdenas, R.P.; Durai, J.; Trinh, T.L.; Li, Y. (International Bamboo and Rattan Organisation (INBAR), 2021)
Two studies on ecosystem services were conducted in the northern and central jungle regions of Peru to better understand the ecosystem services that are provided by different land uses in the region. Through surveys conducted with the participation of local and regional actors, three types of land use (bamboo forest/plantation, natural forest and farm) were studirkiinwwored to evaluate ecosystem benefits.